Utilization Of Educational Media In Language Learning - Awal Kurnia Putra Nasution (Asosiasi Dosen Perguruan Tinggi Islam, 2021)
Educational media is one of the aspects that determine the success of learning. Language learning uses specific learning media because it requires a unique approach. The purpose of this study was to determine the educational media used in language learning and their effectiveness. The research method used is a literature review; the article's source comes from the Scopus database. The number of articles used as data sources is 16 articles. The study results found that the learning media used in language learning were: social media, Facebook, website, mobile learning, and Android. The entire educational media utilizes technology. Only one educational medium was found that did not utilize technology, namely the use of musical instruments. The results showed that the educational media used was effective. The use of educational technology in learning provides opportunities for further development in its use strategy.